2022 IEEE International Conference on Image Processing (ICIP) 2022
DOI: 10.1109/icip46576.2022.9897283
|View full text |Cite
|
Sign up to set email alerts
|

Anomalib: A Deep Learning Library for Anomaly Detection

Abstract: This paper introduces anomalib 1 , a novel library for unsupervised anomaly detection and localization. With reproducibility and modularity in mind, this open-source library provides algorithms from the literature and a set of tools to design custom anomaly detection algorithms via a plug-andplay approach. Anomalib comprises state-of-the-art anomaly detection algorithms that achieve top performance on the benchmarks and that can be used off-the-shelf. In addition, the library provides components to design cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In the training process, "m" refers to the defect sample used. It is worth mentioning that the unsupervised algorithms were implemented using the open-source industrial defect detection library anomalib [46]. Combining the data from Tables 1 and 2, it can be observed that our proposed method outperforms other unsupervised industrial defect detection algorithms in terms of imagelevel classification ROC, except for PatchCore.…”
Section: Comparison With Unsupervised-based Algorithmmentioning
confidence: 84%
“…In the training process, "m" refers to the defect sample used. It is worth mentioning that the unsupervised algorithms were implemented using the open-source industrial defect detection library anomalib [46]. Combining the data from Tables 1 and 2, it can be observed that our proposed method outperforms other unsupervised industrial defect detection algorithms in terms of imagelevel classification ROC, except for PatchCore.…”
Section: Comparison With Unsupervised-based Algorithmmentioning
confidence: 84%
“…Furthermore, we also compared our method to those that utilize external priors, such as S-T, SPADE, etc. All methods were reproduced based on the official implementation or AnomaLib [1]. For fair comparisons, we adapted the 1 × 1 convolution W to the pre-trained encoder, where the pre-trained encoder is the first two layers of ResNet18 for extracting the image into features of original 1/4 size and with 64 channels.…”
Section: Anomaly Localizationmentioning
confidence: 99%
“…For the TILDA dataset, we restructured the data to conform to the MVTEC nomenclature. To ensure a fair comparison with state-of-the-art methods, the anomalib library 46 was employed. The results are shown in Table 4 and Figure 7.…”
Section: State Of the Art Auroc Comparisonmentioning
confidence: 99%